Defect catalyst and preparation method and application thereof
By preparing a defect catalyst by loading silver oxide onto a titanium dioxide support, the problem of N-VOCs being difficult to convert into NH3 was solved, achieving efficient N-VOCs conversion and ammonia production, reducing costs and facilitating industrial application.
Patent Information
- Application Number
- CN202411422827.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-10-12
AI Technical Summary
Existing catalysts have difficulty converting intermediate products into ammonia (NH3) when degrading nitrogen-containing volatile organic compounds (N-VOCs), resulting in insufficient resource utilization of N-VOCs.
A defective catalyst was prepared by using defective titanium dioxide as a support and silver oxide as the active center through hydrolysis and alkaline etching. This increased the specific surface area and acidic sites of the catalyst, promoted the breaking of CN bonds, and enabled the intermediate product to be converted into NH3.
This method achieves efficient conversion of N-VOCs and efficient production of ammonia, reduces catalyst production costs, improves the conversion rate of N-VOCs and the yield of NH3, and is simple and easy to industrialize.
Smart Images

Figure CN119281322A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of catalytic degradation of nitrogen-containing volatile organic matter, and specifically relates to a defective catalyst and a preparation method and application thereof, and in particular to a defective catalyst for catalytic degradation of nitrogen-containing volatile organic matter and synergistic ammonia production and a preparation method and application thereof. Background Art
[0002] Nitrogen-containing volatile organic compounds (N-VOCs) are the most common organic waste gases emitted by petrochemical, pharmaceutical, steel and other industries. N-VOCs have many subtypes, mainly including pollutants such as aliphatic amines, aromatic amines, amides, alcohol amines, nitriles and nitro groups. Due to the presence of nitrogen, their odor and toxicity are stronger than ordinary aromatic hydrocarbons and oxidizing organic compounds, which will cause serious pollution and harm to the environment and human body. It is urgent to reduce and control their emissions, but their treatment is much more difficult than general volatile organic compounds (VOCs).
[0003] At present, the methods for reducing N-VOCs emissions in industry include physical adsorption, physical condensation, combustion oxidation, catalytic oxidation, and microbial degradation. Among them, the combustion oxidation method is more common, but the process usually needs to be operated at high temperature, and a large amount of nitrogen oxides are generated during the reaction. The catalytic oxidation method can not only reduce the operating temperature of the combustion oxidation method, but also achieve the resource utilization and green utilization of "N" in N-VOCs by regulating the catalyst. Therefore, the catalytic oxidation method is more popular in the process of removing N-VOCs. However, when existing catalysts degrade N-VOCs, they generally convert intermediate products into N2 and / or nitrogen oxides. There are few studies on converting "N" in N-VOCs into NH3, which can be used as a zero-carbon energy carrier.
[0004] For example, Guo Yanglong et al. studied an Ag / Ce-Zr catalyst for the catalytic combustion of nitrogen-containing volatile organic matter. By adjusting the doping amount of Zr, a series of Ag / Ce-Zr solid solution catalysts with adjustable redox performance and acidity were synthesized for the catalytic combustion reaction of N,N-dimethylformamide (DMF). However, it converts organic intermediates into N2 and does not realize the resource utilization of ammonia (see Guo et al. Ag / Ce-Zr catalyst for catalytic combustion of nitrogen-containing volatile organic matter: balance between redox performance and acidity. Rare Metals. (2024).).
[0005] CN118059930A discloses a catalytic oxidation catalyst and a preparation method thereof, as well as a method for treating nitrogen-containing VOCs. The catalytic oxidation catalyst contains a mixture of catalyst A and catalyst B, wherein the catalyst A contains a first carrier and a first active component loaded on the first carrier, and the catalyst B contains a second carrier and a second active component loaded on the second carrier, wherein the first active component is one or more of Pt, Pd and Ag, and the second active component is one or more of Mn, Fe, Co and Cu, and the weight ratio of the catalyst A to the catalyst B is 1:0.2-5. However, the catalyst still mainly converts ethylenediamine into N2, and does not simultaneously achieve the conversion of N-VOCs and the resource utilization of "N".
[0006] Therefore, in view of the above defects, there is an urgent need to develop a catalyst and a preparation method thereof that can be used to efficiently degrade N-VOCs and convert the "-NH2" in N-VOCs into NH3, so as to achieve N-VOCs emission reduction control and resource utilization of ammonia. Summary of the invention
[0007] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a defective catalyst for catalytic degradation of nitrogen-containing volatile organic compounds and synergistic production of ammonia, as well as a preparation method and application thereof, with defective titanium dioxide as a carrier and silver oxide as an active center, to form a defective catalyst with high specific surface area and high catalytic activity; and used for catalytic degradation of N-VOCs and synergistic production of ammonia, achieving efficient conversion of N-VOCs and efficient output of ammonia, and the preparation process of the defective catalyst is simple, the raw materials are cheap, the production cost is low, and it is easy to industrialize.
[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a defective catalyst, comprising a defective titanium dioxide carrier and a metal oxide active center supported on the defective titanium dioxide carrier; the metal oxide active center comprises silver oxide.
[0010] The defective titanium dioxide carrier in the defective catalyst of the present invention has surface defects, has a high specific surface area, and can effectively regulate the acid sites on the surface of the obtained catalyst and the morphology of the metal active center on its surface. The surface defects increase the metal anchoring sites on the surface of the carrier, so that the active center exists in the form of silver oxide, presenting as Ag2O atomic clusters; the defective titanium dioxide carrier and the silver oxide active center act synergistically, Ag2O promotes the breaking of the CN bond, thereby promoting the conversion of the intermediate product into NH3, and the surface defects increase the number of Lewis acids on the surface of the obtained catalyst, promote the desorption of NH3, and prevent further oxidation, thereby finally achieving the emission reduction control of N-VOCs and the green resource utilization of nitrogen resources.
[0011] Preferably, the crystal form of the defective titanium dioxide carrier includes anatase.
[0012] The present invention further prefers that the crystal form of the defective titanium dioxide carrier includes anatase type. The anatase type has a large specific surface area and many acidic sites, which is more conducive to catalytic degradation of N-VOCs and coordinated production of NH3.
[0013] Preferably, the specific surface area of the defective titanium dioxide carrier is 195.658 to 220.895 m 2 / g, for example, it can be 195.658m 2 / g, 200.156m 2 / g, 205.248m 2 / g, 210.456m 2 / g, 215.720m 2 / g, 219.285m 2 / g or 220.895m 2 / g, etc.
[0014] Preferably, the mass ratio of the metal oxide active centers to the defective titanium dioxide carrier in the defective catalyst is 1:(99-100), for example, it can be 1:99, 1:99.2, 1:99.4, 1:99.6, 1:99.8 or 1:100, etc.
[0015] The present invention further preferably has a mass ratio of metal oxide active centers to defective titanium dioxide carriers in the defective catalyst of 1:(99-100), that is, a higher catalytic activity can be achieved only under conditions of a lower metal oxide active center loading, thereby reducing the catalyst production cost and the cost of catalytic degradation of N-VOCs.
[0016] Preferably, the specific surface area of the defective catalyst is 165.326 to 200.235 m 2 / g, for example, it can be 165.326m 2 / g, 180.569m2 / g, 185.324m 2 / g, 190.145m 2 / g, 195.227m 2 / g, 198.471m 2 / g or 200.235m 2 / g, etc.
[0017] The present invention further prefers that the specific surface area of the defective titanium dioxide carrier is increased by about 3 times compared with ordinary silicon dioxide, thereby increasing the specific surface area of the obtained defective catalyst, thereby increasing its adsorption capacity for N-VOCs and achieving a higher conversion rate of N-VOCs.
[0018] In a second aspect, the present invention provides a method for preparing the defective catalyst according to the first aspect, the preparation method comprising the following steps:
[0019] (1) mixing a titanium source, a silicon source and a solvent and hydrolyzing them to obtain a titanium-silicon composite carrier;
[0020] (2) mixing the titanium-silicon composite support described in step (1) with an alkaline solution and etching the mixture to obtain the defective titanium dioxide support;
[0021] (3) Mixing and impregnating the defective titanium dioxide carrier described in step (2) with a metal oxide precursor solution to obtain the defective catalyst.
[0022] The present invention firstly adopts a method of combining hydrolysis with alkaline etching to prepare a defective titanium dioxide carrier, generates defects through alkaline etching, and then combines a mixed impregnation method to load metal oxide active centers on the defective titanium dioxide carrier, wherein the defects generated by alkaline etching can not only effectively regulate the active centers to exist in the form of oxides on the surface of the defective titanium dioxide carrier, but also regulate the acidic sites on the surface of the obtained defective catalyst and increase the specific surface area, which is beneficial to the efficient catalytic degradation of N-VOCs. At the same time, it can also convert the intermediate product containing -NH2 into NH3, thereby realizing the efficient and green degradation of N-VOCs and the effective utilization of nitrogen resources.
[0023] Preferably, the titanium source in step (1) comprises tetrabutyl titanate.
[0024] Preferably, the silicon source in step (1) comprises tetraethyl silicate.
[0025] Preferably, the molar ratio of the titanium source to the silicon source in step (1) is (4.5-5.5):1, for example, it can be 4.5:1, 4.7:1, 5.0:1, 5.2:1 or 5.5:1.
[0026] The present invention further preferably has a molar ratio of the titanium source to the silicon source in step (1) of (4.5-5.5):1, which is conducive to the subsequent formation of surface defects by etching to obtain a defective titanium dioxide carrier; if the silicon source content is too high, the alkali concentration will increase during the etching process, resulting in alkali residues during subsequent treatments, and will also interfere with the growth of titanium dioxide crystals, resulting in the formation of an amorphous titanium dioxide carrier; if the silicon source content is too low, the surface defects will be too few, and the formed carrier will be equivalent to ordinary titanium dioxide, resulting in poor catalytic effect and NH3 production effect.
[0027] Preferably, the solvent comprises water and / or ethanol.
[0028] Preferably, the volume ratio of the sum of the titanium source and the silicon source to the solvent in step (1) is 1:(2.5-3.5), for example, it can be 1:2.5, 1:2.8, 1:3.0, 1:3.2 or 1:3.5, etc.
[0029] Preferably, the hydrolysis process in step (1) is accompanied by stirring.
[0030] Preferably, the hydrolysis time in step (1) is 10 to 15 hours, for example, it can be 10 hours, 11 hours, 12 hours, 13 hours, 14 hours or 15 hours.
[0031] Preferably, after the hydrolysis in step (1), a titanium-silicon composite carrier suspension is first obtained, and then the titanium-silicon composite carrier suspension is subjected to a first rotary evaporation and a first calcination in sequence to obtain the titanium-silicon composite carrier.
[0032] Preferably, the temperature of the first rotary evaporation is 50-70°C, for example, 50°C, 55°C, 60°C, 65°C or 70°C.
[0033] Preferably, the rotation speed of the first rotary evaporation is 50-80 r / min, for example, it can be 50 r / min, 55 r / min, 60 r / min, 65 r / min, 70 r / min, 75 r / min or 80 r / min.
[0034] Preferably, the heating rate of the first calcination is 8-12°C / min, for example, 8°C / min, 9°C / min, 10°C / min, 11°C / min or 12°C / min.
[0035] Preferably, the heating end point temperature of the first calcination is 450-650°C, for example, 450°C, 500°C, 550°C, 600°C or 650°C.
[0036] Preferably, the holding time of the first calcination is 3 to 6 hours, for example, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours or 6 hours.
[0037] Preferably, after the titanium-silicon composite carrier suspension is subjected to a first rotary evaporation, a first drying is performed first, and then a first calcination is performed.
[0038] Preferably, the first drying temperature is 80-100°C, for example, 80°C, 85°C, 90°C, 95°C or 100°C.
[0039] Preferably, the first drying time is 4 to 12 hours, for example, 4 hours, 6 hours, 8 hours, 10 hours or 12 hours.
[0040] Preferably, the alkaline solution in step (2) comprises any one of sodium hydroxide solution, ammonia water or potassium hydroxide solution, or a combination of at least two of them, wherein typical but non-limiting combinations include a combination of sodium hydroxide solution and ammonia water, a combination of ammonia water and potassium hydroxide solution, or a combination of sodium hydroxide solution and potassium hydroxide solution, etc.
[0041] Preferably, the concentration of the alkaline solution in step (2) is 1.8 to 2.2 mol / L, for example, 1.8 mol / L, 2.0 mol / L or 2.2 mol / L.
[0042] Preferably, the solid-to-liquid ratio of the titanium-silicon composite carrier to the alkaline solution in step (2) is 1:(10-20) g / mL, for example, it can be 1:10 g / mL, 1:12 g / mL, 1:14 g / mL, 1:16 g / mL, 1:18 g / mL or 1:20 g / mL, etc.
[0043] The present invention further prefers that the solid-liquid ratio of the titanium-silicon composite support to the alkaline solution in step (2) is 1: (10-20) g / mL, which is conducive to fully etching the titanium-silicon composite support and generating more defects, thereby increasing the surface area of the defective titanium dioxide support, and further increasing the catalytic activity of the obtained defective catalyst and fully regulating the subsequent active centers to exist in the form of oxides; if the solid-liquid ratio of the titanium-silicon composite support to the alkaline solution is too large, that is, the alkaline solution is too small, it will lead to insufficient alkaline etching, thereby resulting in a reduction in the defects of the defective titanium dioxide support and a reduction in the active centers on its surface in the form of oxides, resulting in a decrease in the catalytic activity of the obtained defective catalyst, and ultimately resulting in a decrease in the N-VOCs conversion rate and a decrease in the NH3 yield; if the solid-liquid ratio of the titanium-silicon composite support to the alkaline solution is too small, that is, the alkaline solution is too large, the N-VOCs conversion rate and the NH3 yield are not significantly improved, but instead cause reagent waste and increase costs.
[0044] Preferably, the etching temperature in step (2) is 40-80°C, for example, it can be 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or 80°C, etc., preferably 40-60°C.
[0045] The present invention further prefers that the etching temperature in step (2) is 40-60°C, which is conducive to the formation of a defective titanium dioxide carrier, thereby facilitating the successful preparation of a defective catalyst and improving the N-VOCs conversion rate and NH3 yield; if the etching temperature is too low, it will lead to insufficient etching, reduced surface defects of the defective titanium dioxide carrier, and reduced active centers in the form of oxides, thereby reducing the subsequent N-VOCs conversion rate and NH3 yield; if the etching temperature is too high, the N-VOCs conversion and NH3 output effects are not significantly improved, but energy consumption is increased.
[0046] Preferably, the etching process in step (2) is accompanied by stirring.
[0047] Preferably, the etching time in step (2) is 10 to 15 hours, for example, it can be 10 hours, 11 hours, 12 hours, 13 hours, 14 hours or 15 hours.
[0048] Preferably, after the etching, a defective titanium dioxide carrier suspension is first obtained, and then the defective titanium dioxide carrier suspension is centrifugally washed and dried in sequence to obtain the defective silicon dioxide carrier;
[0049] Preferably, the washing liquid of the centrifugal washing comprises water and / or ethanol.
[0050] Preferably, the endpoint of the centrifugal washing is that the pH of the supernatant is 7.0 to 7.5, for example, 7.0, 7.2, 7.3, 7.4 or 7.5.
[0051] The purpose of the centrifugal washing of the present invention is to remove the alkaline solution remaining on the surface.
[0052] Preferably, the second drying temperature is 80-100°C, for example, 80°C, 85°C, 90°C, 95°C or 100°C.
[0053] Preferably, the second drying time is 4 to 12 hours, for example, 4 hours, 6 hours, 8 hours, 10 hours or 12 hours.
[0054] Preferably, the temperature of the mixed impregnation in step (3) is 40-80°C, for example, it can be 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or 80°C.
[0055] Preferably, the mixed impregnation time in step (3) is 1 to 3 hours, for example, it can be 1 hour, 1.5 hours, 2 hours, 2.5 hours or 3 hours.
[0056] Preferably, the mixed impregnation process in step (3) is accompanied by stirring.
[0057] Preferably, the metal oxide precursor solution in step (3) comprises AgNO3 solution.
[0058] Preferably, the mass ratio of the metal oxide precursor to the defective titanium dioxide support in the metal oxide precursor solution in step (3) is 1:(99-100), for example, it can be 1:99, 1:99.2, 1:99.4, 1:99.6, 1:99.8 or 1:100, etc.
[0059] The present invention further preferably has a mass ratio of the metal oxide precursor to the defective titanium dioxide carrier in the metal oxide precursor solution in step (3) of 1:(99-100), that is, under conditions of a lower metal oxide loading, a higher N-VOCs conversion rate and NH3 yield can be obtained at a lower cost.
[0060] Preferably, after the mixed impregnation, a mixed impregnation liquid is first obtained, and then the mixed impregnation liquid is subjected to a second rotary evaporation and a second calcination in sequence to obtain the defective catalyst.
[0061] Preferably, the temperature of the second rotary evaporation is 40-80°C, for example, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or 80°C.
[0062] Preferably, the rotation speed of the second rotary evaporation is 50-80 r / min, for example, it can be 50 r / min, 55 r / min, 60 r / min, 65 r / min, 70 r / min, 75 r / min or 80 r / min.
[0063] Preferably, the second rotary evaporation time is 0.5 to 1 h, for example, 0.5 h, 0.6 h, 0.7 h, 0.8 h or 1 h.
[0064] Preferably, the heating rate of the second calcination is 8-12°C / min, for example, 8°C / min, 9°C / min, 10°C / min, 11°C / min or 12°C / min.
[0065] Preferably, the heating end point temperature of the second calcination is 250-350°C, for example, 250°C, 280°C, 300°C, 320°C or 350°C.
[0066] Preferably, the holding time of the second calcination is 3 to 6 hours, for example, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours or 6 hours.
[0067] Preferably, after the mixed impregnation liquid is subjected to a second rotary evaporation, it is sequentially subjected to a third drying and a second calcination to obtain the defective catalyst.
[0068] Preferably, the third drying temperature is 90-120°C, for example, 90°C, 100°C, 110°C or 120°C.
[0069] Preferably, the third drying time is 8 to 12 hours, for example, 8 hours, 9 hours, 10 hours, 11 hours or 12 hours.
[0070] As a further preferred technical solution of the present invention, according to Figure 1 The process flow shown in the figure is carried out, and the preparation method of the defective catalyst comprises the following steps:
[0071] (1) mixing a titanium source and a silicon source in a molar ratio of (4.5-5.5):1 with a solvent and hydrolyzing them to obtain a titanium-silicon composite carrier suspension; then subjecting the titanium-silicon composite carrier suspension to a first rotary evaporation at 50-70°C and 50-80 r / min, and then heating the suspension to 450-650°C at a heating rate of 8-12°C / min and keeping the temperature for 3-6 hours to perform a first calcination to obtain the titanium-silicon composite carrier;
[0072] The volume ratio of the sum of the titanium source and the silicon source to the first solvent is 1:(2.5-3.5);
[0073] (2) mixing the titanium-silicon composite support of step (1) with an alkaline solution having a concentration of 1.8 to 2.2 mol / L at a solid-liquid ratio of 1:(10 to 20) g / mL, etching for 10 to 15 h at 40 to 80° C. with stirring, and then centrifugally washing and drying in sequence to obtain the defective titanium dioxide support;
[0074] (3) impregnating the defective titanium dioxide support and the metal oxide precursor solution in step (2) at 40 to 80° C. for 1 to 3 hours to obtain a mixed impregnation solution; performing a second rotary evaporation at 40 to 80° C. and 50 to 80 r / min; then heating the temperature to 250 to 350° C. at a heating rate of 8 to 12° C. / min and maintaining the temperature for 3 to 6 hours to perform a second calcination to obtain the defective catalyst;
[0075] The mass ratio of the metal oxide precursor in the metal oxide precursor solution to the defective titanium dioxide carrier is 1:(99-100).
[0076] In a third aspect, the present invention provides a method for catalytic degradation of nitrogen-containing volatile organic matter and synergistic production of ammonia, the method being carried out using the defective catalyst described in the first aspect; the method comprising the following steps: nitrogen-containing volatile organic matter is degraded by catalytic reaction under the action of the defective catalyst to produce ammonia.
[0077] The present invention uses the defective catalyst described in the first aspect to catalyze the degradation of the nitrogen-containing volatile organic matter and synergistically produce ammonia, thereby achieving efficient conversion of N-VOCs and efficiently converting the intermediate product containing -NH2 into NH3, avoiding N-VOCs pollution while achieving green resource utilization of nitrogen resources. The method is simple, and the temperature for achieving the highest conversion rate of N-VOCs and the highest yield of NH3 is relatively low, and the amount of catalyst required is relatively small, that is, the reaction energy consumption and cost are relatively low.
[0078] Preferably, the nitrogen-containing volatile organic compound includes any one of ethanolamine, N,N-dimethylethanolamine or N,N-dimethylamide, or a combination of at least two of them, wherein typical but non-limiting combinations include a combination of ethanolamine and N,N-dimethylethanolamine, a combination of N,N-dimethylethanolamine and N,N-dimethylamide, or a combination of ethanolamine and N,N-dimethylamide, etc.
[0079] Preferably, the gas volume space velocity of the catalytic reaction is 50000~70000h -1 , for example, it can be 50000h -1 、60000h -1 or 70000h -1 .
[0080] Preferably, the temperature of the catalytic reaction is 80-300°C, for example, it can be 80°C, 100°C, 120°C, 150°C, 180°C, 200°C, 220°C, 250°C, 280°C or 300°C, preferably 220-280°C.
[0081] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0082] Compared with the prior art, the present invention has the following beneficial effects:
[0083] (1) The defective catalyst provided by the present invention uses defective titanium dioxide as a carrier and silver oxide as an active center. The synergistic effect of the two makes the defective catalyst have a high specific surface area and high catalytic activity, thereby achieving efficient degradation of N-VOCs. At the same time, it can also convert the -NH2-containing intermediate products generated during the degradation of N-VOCs into NH3, thereby achieving N-VOCs emission reduction control and green resource utilization of nitrogen resources. In addition, the defective catalyst is low-priced, non-toxic, easy to separate and recycle, and has broad application prospects.
[0084] (2) The preparation method of the defective catalyst provided by the present invention first successfully prepares a defective titanium dioxide carrier by combining a hydrolysis method and an alkaline etching method, and then uses a mixed impregnation method to attach metal oxide active centers to the defective titanium dioxide carrier, thereby successfully preparing a defective catalyst that exhibits high catalytic activity in the catalytic degradation of N-VOCs and can convert intermediate products into NH3. Then, by further optimizing parameters such as the solid-liquid ratio and the etching temperature in the preparation process, the conversion rate of the catalytic degradation of N-VOCs and the efficiency of producing NH3 are further improved. The preparation method has a wide range of raw material sources, a simple and controllable preparation process, and is easy to industrialize.
[0085] (3) The present invention provides a method for catalytic degradation of nitrogen-containing volatile organic compounds and coordinated production of ammonia. The method uses the defective catalyst as described above to obtain a higher N-VOCs conversion rate and NH3 yield. The N-VOCs conversion rate is preferably as high as 98.0% or more, and the NH3 yield is preferably as high as 100%; and the temperature required to achieve the highest N-VOCs conversion rate is preferably as low as below 230°C; the temperature required to achieve the highest NH3 yield is as low as 280°C; the method requires a relatively small amount of defective catalyst, is non-toxic and harmless, and is environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0086] Figure 1 It is a process flow chart of the preparation method of the defective catalyst provided by the present invention;
[0087] Figure 2 is a synchrotron radiation R space fitting diagram of the defective catalyst Ag2O / TiO2-D provided in Example 1 of the present invention;
[0088] Figure 3 This is the synchrotron radiation R space fitting diagram of the silver oxide standard sample. DETAILED DESCRIPTION
[0089] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0090] The experimental methods in the following embodiments and comparative examples, application examples and comparative application examples are all conventional methods unless otherwise specified; the experimental materials used are all purchased from conventional biochemical reagent manufacturers unless otherwise specified.
[0091] 1. Implementation
[0092] Example 1
[0093] This embodiment provides a method for preparing a defective catalyst, the preparation method comprising the following steps:
[0094] (1) Tetrabutyl titanate and tetraethyl silicate in a molar ratio of 5:1 were mixed with 300 mL of water and stirred for hydrolysis to obtain a titanium-silicon composite carrier suspension; the titanium-silicon composite carrier suspension was subjected to a first rotary evaporation at 60° C. and 60 r / min, and then the temperature was increased to 500° C. at a heating rate of 10° C. / min and kept for 4 h for a first calcination to obtain the titanium-silicon composite carrier;
[0095] The volume ratio of the sum of tetrabutyl titanate and tetraethyl silicate to water is 1:3;
[0096] (2) According to the solid-liquid ratio of 1:18.75 g / mL, 16 g of the titanium-silicon composite carrier of step (1) was mixed with 300 mL of a 2 mol / L sodium hydroxide solution, and the mixture was etched at 50° C. with stirring for 12 h, and then centrifuged and washed with water and dried at 100° C. for 4 h to obtain the defective titanium dioxide carrier;
[0097] (3) The defective titanium dioxide carrier and the AgNO3 solution of step (2) are mixed and impregnated at 50°C with stirring for 2 hours to obtain a mixed impregnation solution; a second rotary evaporation is then performed at 60°C and 60 r / min; the temperature is then increased to 300°C at a heating rate of 10°C / min and kept warm for 4 hours to perform a second calcination to obtain the defective catalyst; the mass ratio of the defective titanium dioxide carrier to the AgNO3 in the AgNO3 solution is 1:99.5.
[0098] The defective catalyst obtained in this example includes a silver oxide active center and a defective titanium dioxide carrier supported on a defective titanium dioxide carrier in a mass ratio of 1:99.5; the crystal form of the defective titanium dioxide carrier is anatase type, and the specific surface area of the defective titanium dioxide carrier is 203.255 m 2 / g, the specific surface area of the defective catalyst is 179.561m 2 / g.
[0099] Depend on Figure 2 and Figure 3It can be seen that: by comparing the R space fitting results of the catalyst Ag2O / TiO2-D obtained in this embodiment with the Ag2O standard sample, it can be seen that the characteristic peak positions of Ag-O and Ag-O-Ag bonds in the defective catalyst are consistent with those of the Ag2O standard sample; thus, it can be confirmed that the active center of the defective catalyst obtained in this embodiment exists in the form of Ag2O.
[0100] Example 2
[0101] This embodiment provides a method for preparing a defective catalyst, the preparation method comprising the following steps:
[0102] (1) Tetrabutyl titanate and tetraethyl silicate in a molar ratio of 4.5:1 were mixed with 300 mL of water and stirred for hydrolysis to obtain a titanium-silicon composite carrier suspension; the titanium-silicon composite carrier suspension was subjected to a first rotary evaporation at 50° C. and 80 r / min, and then the temperature was increased to 650° C. at a heating rate of 8° C. / min and kept for 3 h for a first calcination to obtain the titanium-silicon composite carrier;
[0103] The volume ratio of the sum of tetrabutyl titanate and tetraethyl silicate to water is 1:2.5;
[0104] (2) Mixing 30 g of the titanium-silicon composite support of step (1) with 300 mL of a 1.8 mol / L sodium hydroxide solution at a solid-liquid ratio of 1:10 g / mL, etching for 15 h at 40 ° C. with stirring, then washing with water by centrifugation and drying at 80 ° C. for 12 h to obtain the defective titanium dioxide support;
[0105] (3) The defective titanium dioxide carrier and the AgNO3 solution of step (2) are mixed and impregnated at 40°C with stirring for 3 hours to obtain a mixed impregnation solution; a second rotary evaporation is then performed at 40°C and 50 r / min; the temperature is then increased to 250°C at a heating rate of 12°C / min and kept warm for 6 hours to perform a second calcination to obtain the defective catalyst; the mass ratio of the defective titanium dioxide carrier to the AgNO3 in the AgNO3 solution is 1:99.
[0106] The defective catalyst obtained in this embodiment includes a silver oxide active center and a defective titanium dioxide carrier supported on a defective titanium dioxide carrier in a mass ratio of 1:99; the crystal form of the defective titanium dioxide carrier is anatase type, and the specific surface area of the defective titanium dioxide carrier is 195.658 m 2 / g, the specific surface area of the defective catalyst is 165.326m 2 / g.
[0107] Example 3
[0108] This embodiment provides a method for preparing a defective catalyst, the preparation method comprising the following steps:
[0109] (1) Tetrabutyl titanate and tetraethyl silicate in a molar ratio of 5.5:1 were mixed with 300 mL of water and stirred for hydrolysis to obtain a titanium-silicon composite carrier suspension; the titanium-silicon composite carrier suspension was subjected to a first rotary evaporation at 70° C. and 50 r / min, and then the temperature was increased to 450° C. at a heating rate of 12° C. / min and kept for 6 h for a first calcination to obtain the titanium-silicon composite carrier;
[0110] The volume ratio of the sum of tetrabutyl titanate and tetraethyl silicate to water is 1:3.5;
[0111] (2) According to the solid-liquid ratio of 1:20 g / mL, 15 g of the titanium-silicon composite carrier of step (1) was mixed with 300 mL of a 2.2 mol / L sodium hydroxide solution, and the mixture was etched at 60° C. with stirring for 10 h, and then centrifuged and washed with water and dried at 100° C. for 4 h to obtain the defective titanium dioxide carrier;
[0112] (3) The defective titanium dioxide carrier and the AgNO3 solution of step (2) are mixed and impregnated at 80°C with stirring for 1 hour to obtain a mixed impregnation solution; a second rotary evaporation is then performed at 80°C and 80 r / min; the temperature is then increased to 350°C at a heating rate of 10°C / min and kept warm for 3 hours to perform a second calcination to obtain the defective catalyst; the mass ratio of the defective titanium dioxide carrier to the AgNO3 in the AgNO3 solution is 1:100.
[0113] The defective catalyst obtained in this embodiment includes a silver oxide active center and a defective titanium dioxide carrier supported on a defective titanium dioxide carrier in a mass ratio of 1:100; the crystal form of the defective titanium dioxide carrier is anatase type, and the specific surface area of the defective titanium dioxide carrier is 201.326 m 2 / g, the specific surface area of the defective catalyst is 199.650m 2 / g.
[0114] Example 4
[0115] This embodiment provides a method for preparing a defective catalyst, which is the same as that of Embodiment 1 except that the molar ratio of tetrabutyl titanate to tetraethyl silicate in step (1) is 4.2:1.
[0116] Example 5
[0117] This embodiment provides a method for preparing a defective catalyst, which is the same as that of Embodiment 1 except that the molar ratio of tetrabutyl titanate to tetraethyl silicate in step (1) is 5.8:1.
[0118] Example 6
[0119] This embodiment provides a method for preparing a defective catalyst, and the preparation method is the same as that of Embodiment 1 except that the solid-liquid ratio of the titanium silicon composite support to the sodium hydroxide solution is 1:9.5 g / mL.
[0120] Example 7
[0121] This embodiment provides a method for preparing a defective catalyst, and the preparation method is the same as that of Embodiment 1 except that the solid-liquid ratio of the titanium silicon composite support to the sodium hydroxide solution is 1:21 g / mL.
[0122] Example 8
[0123] This embodiment provides a method for preparing a defective catalyst. The preparation method is the same as that of Embodiment 1 except that the etching temperature in step (2) is 35°C.
[0124] Example 9
[0125] This embodiment provides a method for preparing a defective catalyst. The preparation method is the same as that of Embodiment 1 except that the etching temperature in step (2) is 80°C.
[0126] Example 10
[0127] This embodiment provides a method for preparing a defective catalyst, and the preparation method is the same as that of Embodiment 1 except that the mass ratio of AgNO3 to the defective titanium dioxide carrier in the AgNO3 solution in step (3) is 1.5:99.
[0128] 2. Comparison
[0129] Comparative Example 1
[0130] This comparative example provides a method for preparing a defective catalyst, which is the same as Example 1 except that the AgNO3 solution in step (3) is replaced by Cu(NO3)2.
[0131] Comparative Example 2
[0132] This comparative example provides a method for preparing a catalyst, which is the same as Example 1 except that step (1) and step (2) are not performed and titanium dioxide and AgNO3 solution are directly mixed and impregnated.
[0133] In this comparative example, since ordinary titanium dioxide is used, after it is mixed and impregnated with the AgNO3 solution, the active center exists in the form of Ag nanoparticles.
[0134] Comparative Example 3
[0135] This comparative example provides a method for preparing a catalyst, which is the same as Example 1 except that only steps (1) and (2) are performed, and step (3) is not performed.
[0136] 3. Application Examples
[0137] The following application examples and comparative application examples were conducted using a Fourier transform infrared detector coupled with a gas mass spectrometer, with a gas volume space velocity of 50,000 to 70,000 h -1 The temperature of the catalytic reaction is 80-300°C.
[0138] Application Example 1
[0139] This application example provides a method for catalytic degradation of ethanolamine to produce ammonia in a coordinated manner, the method comprising the following steps: introducing an oxygen content of 20% (N2 as carrier gas) and a volume space velocity of 60000h -1 Under the above conditions, ethanolamine with a concentration of 200 ppm is degraded by the defective catalyst provided in Example 1 through catalytic reaction and produces NH3.
[0140] Application Example 2
[0141] This application example provides a method for catalytic degradation of ethanolamine to produce ammonia in a coordinated manner, the method comprising the following steps: introducing an oxygen content of 15% (N2 as carrier gas) and a volume space velocity of 50000h -1 Under the above conditions, ethanolamine with a concentration of 180 ppm and the defective catalyst provided in Example 2 were degraded by catalytic reaction and NH3 was produced.
[0142] Application Example 3
[0143] This application example provides a method for catalytic degradation of ethanolamine to produce ammonia in a coordinated manner, the method comprising the following steps: introducing an oxygen content of 25% (N2 as carrier gas) and a volume space velocity of 70000h -1 Under the above conditions, ethanolamine with a concentration of 220 ppm and the defective catalyst provided in Example 3 were degraded by catalytic reaction and NH3 was produced.
[0144] Application Examples 4 to 10
[0145] The other conditions are kept the same as those in Application Example 1, and only the defective catalyst used is changed. Specifically, Application Examples 4 to 10 use the defective catalysts prepared in Examples 4 to 10 in sequence.
[0146] 4. Comparative Application Examples
[0147] Comparative Application Examples 1 to 3
[0148] The other conditions were kept the same as those in Application Example 1, and only the catalyst used was changed. Specifically, Comparative Application Examples 1 to 3 used the catalysts prepared in Comparative Examples 1 to 3 in sequence.
[0149] Comparative Application Example 4
[0150] This comparative example provides a method for catalytic degradation of ethanolamine to produce ammonia in coordination. The method is the same as that of Application Example 1 except that TiO2 is used as a catalyst.
[0151] Comparative Application Example 5
[0152] This comparative application example provides a method for catalytic degradation of ethanolamine. The method is the same as Application Example 1 except that no catalyst is used and only 20% oxygen (N2 as carrier gas) is introduced.
[0153] Comparative Application Example 6
[0154] This comparative application example provides a method for catalytic degradation of ethanolamine, which is the same as Application Example 1 except that no catalyst is used and only 50 ppm CO2 (N2 is used as a carrier gas) is introduced.
[0155] Comparative Application Example 7
[0156] This comparative application example provides a method for catalytic degradation of ethanolamine, which is the same as Application Example 1 except that no catalyst is used and only 200 ppm CO2 (N2 is used as a carrier gas) is introduced.
[0157] Comparative Application Example 8
[0158] This comparative application example provides a method for catalytic degradation of ethanolamine, which is the same as Application Example 1 except that no catalyst is used and only 400 ppm CO2 (N2 is used as a carrier gas) is introduced.
[0159] V. Test and its results
[0160] The maximum conversion rate of ethanolamine and the required catalytic temperature in the method for synergistically producing ammonia by catalytic degradation of ethanolamine provided in the above application examples and comparative application examples, as well as the conversion rate of ethanolamine at 220° C. and the yield of NH3 at 220° C. were tested and calculated, and the results are shown in Table 1;
[0161] Table 1
[0162]
[0163]
[0164] Here, “ / ” indicates no NH3 production.
[0165] From the data in Table 1, we can see that:
[0166] (1) It can be seen from the comprehensive application examples 1 to 3 that the defective catalyst prepared by the present invention using defective titanium dioxide as a carrier and silver oxide as an active center can be used to catalyze the degradation of N-VOCs and synergistically produce NH3, and a relatively high ethanolamine conversion rate and NH3 yield rate are obtained. At 220°C, the ethanolamine conversion rate is as high as more than 98.0%, and the NH3 yield is as high as more than 52.8%; and the temperature required to achieve the highest conversion rate is as low as below 230°C, and the temperature required to achieve the highest NH3 yield is as low as 280°C.
[0167] (2) Comprehensively considering Application Example 1 and Application Examples 4 to 5, it can be seen that compared with Application Example 1, the molar ratio of tetrabutyl titanate to tetraethyl silicate in Application Example 4 is relatively small, resulting in the conversion rate of ethanolamine at 220°C decreasing to 87.6%, the NH3 yield decreasing to 35.6%, and the temperature required to reach the highest ethanolamine and the highest NH3 yields both increased; while the molar ratio of tetrabutyl titanate to tetraethyl silicate in Application Example 5 is relatively large, resulting in the conversion rate of ethanolamine at 220°C decreasing to 90.6%, the NH3 yield decreasing to 50.3%, and the temperature required to reach the highest ethanolamine and the highest NH3 yields both increased; thus, it can be seen that the present invention further preferably has a molar ratio of the titanium source to the silicon source in the defective catalyst preparation process of (4.5 to 5.5):1, which further improves the catalytic activity of the obtained defective catalyst, thereby improving the conversion of N-VOCs and the NH3 production effect.
[0168] (3) It can be seen from the combined application examples 1 and 6 to 9 that, compared with application example 1, the solid-liquid ratio of the titanium-silicon composite support to the sodium hydroxide solution in application example 6 is relatively large, resulting in a decrease in the conversion rate of ethanolamine to 95.6% and a decrease in the NH3 yield to 51.0% at 220°C, and an increase in the temperature required to achieve the highest ethanolamine and highest NH3 yields; while the solid-liquid ratio of the titanium-silicon composite support to the sodium hydroxide solution in application example 7 is relatively small, and the effect of catalytic degradation of ethanolamine and production of NH3 is not significantly improved, which will cause reagent waste; the etching described in application example 8 The temperature is relatively low, resulting in the conversion rate of ethanolamine at 220°C decreasing to 73.2%, the NH3 yield decreasing to 27.5%, and the temperature required to achieve the highest ethanolamine and highest NH3 yields increasing; while when the etching temperature in Application Example 9 is relatively high, the effect is not significantly improved, but rather causes greater energy consumption; thus, it can be seen that the present invention further prefers that the solid-liquid ratio of alkaline etching in the preparation process of the defective catalyst is 1:(10-20) g / mL and the temperature is 40-60°C, which further improves the effect of catalytic degradation of N-VOCs and coordinated production of NH3.
[0169] (4) It can be seen from Application Example 1 and Application Examples 10 to 11 that, compared with Application Example 1, when the AgNO3 loading amount in the AgNO3 solution described in Application Example 10 is higher, the catalytic degradation and NH3 production effects are not significantly improved. This shows that the defective catalyst described in the present invention can achieve a higher N-VOCs conversion rate and NH3 yield at a lower loading amount of the metal oxide active center.
[0170] (5) Comprehensive application example 1 and comparative application examples 1 to 4 show that, since Cu(NO3)2 solution is used in comparative application example 1, the active center is CuO, and although ethanolamine can be degraded, NH3 cannot be produced; the carrier titanium dioxide used in comparative application example 2 has no defects, resulting in a small specific surface area, and the surface acid site regulation effect is limited, and the active center exists in the form of silver nanoparticles, resulting in a lower conversion rate of ethanolamine and lower NH3 at the same temperature compared with application example 1; the required temperature is higher at the same conversion rate and NH3 yield; in comparative application example 3, since no silver oxide active center is loaded, the catalytic effect and NH3 production effect are deteriorated; in comparative application example 4, ordinary titanium dioxide is used, no defects are generated, and there is no silver oxide active center, resulting in poor catalytic effect and NH3 production effect.
[0171] (6) It can be seen from the combined application example 1 and the comparative application examples 5 to 8 that in the comparative application examples 5 to 8, the N-VOCs cannot be completely degraded under the conditions of pure oxygen or different concentrations of CO2 without any catalyst, and the ethanolamine conversion rate is as low as below 42.0% at 300°C, or even almost no degradation, and the intermediate products cannot be converted into NH3, and the efficient degradation of N-VOCs and the synergistic production of NH3 cannot be achieved.
[0172] The applicant declares that the present invention illustrates the technical solution of the present invention through the above specific implementation methods, but the present invention is not limited thereto, that is, it does not mean that the present invention must rely on the above embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
[0173] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0174] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
Claims
1. A defective catalyst, characterized in that: The defective catalyst comprises a defective titanium dioxide carrier and a metal oxide active center supported on the defective titanium dioxide carrier; the metal oxide active center comprises silver oxide.
2. The defective catalyst according to claim 1, characterized in that The crystal form of the defective titanium dioxide carrier includes anatase type; Preferably, the specific surface area of the defective titanium dioxide carrier is 195.658 to 220.895 m 2 / g.
3. The defective catalyst according to claim 1 or 2, characterized in that: The mass ratio of the metal oxide active center to the defective titanium dioxide carrier in the defective catalyst is 1:(99-100); Preferably, the specific surface area of the defective catalyst is 165.326 to 200.235 m 2 / g.
4. A method for preparing a defective catalyst according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: (1) mixing a titanium source, a silicon source and a solvent and hydrolyzing them to obtain a titanium-silicon composite carrier; (2) mixing the titanium-silicon composite support described in step (1) with an alkaline solution and etching the mixture to obtain the defective titanium dioxide support; (3) Mixing and impregnating the defective titanium dioxide carrier described in step (2) with a metal oxide precursor solution to obtain the defective catalyst.
5. The preparation method according to claim 4, characterized in that: The titanium source in step (1) includes tetrabutyl titanate; Preferably, the silicon source in step (1) comprises tetraethyl silicate; Preferably, the molar ratio of the titanium source to the silicon source in step (1) is (4.5-5.5):1; Preferably, in step (1), the volume ratio of the sum of the titanium source and the silicon source to the solvent is 1:(2.5-3.5); Preferably, after the hydrolysis in step (1), a titanium-silicon composite carrier suspension is first obtained, and then the titanium-silicon composite carrier suspension is subjected to a first rotary evaporation and a first calcination in sequence to obtain the titanium-silicon composite carrier; Preferably, the temperature of the first rotary evaporation is 50-70°C; Preferably, the rotation speed of the first rotary evaporation is 50-80 r / min; Preferably, the heating rate of the first calcination is 8-12°C / min; Preferably, the first calcination end point temperature is 450-650°C; Preferably, the holding time of the first calcination is 3 to 6 hours.
6. The preparation method according to claim 4 or 5, characterized in that: The alkaline solution in step (2) comprises any one of sodium hydroxide solution, ammonia water or potassium hydroxide solution or a combination of at least two thereof; Preferably, the concentration of the alkaline solution in step (2) is 1.8 to 2.2 mol / L; Preferably, in step (2), the solid-liquid ratio of the titanium-silicon composite support to the alkaline solution is 1:(10-20) g / mL; Preferably, the etching temperature in step (2) is 40 to 80° C., preferably 40 to 60° C.; Preferably, the etching process in step (2) is accompanied by stirring; Preferably, the etching time in step (2) is 10 to 15 hours.
7. The preparation method according to any one of claims 4 to 6, characterized in that: The temperature of the mixed impregnation in step (3) is 40 to 80° C. Preferably, the mixed impregnation time in step (3) is 1 to 3 hours; Preferably, the metal oxide precursor solution in step (3) comprises AgNO3 solution; Preferably, the mass ratio of the metal oxide precursor to the defective titanium dioxide support in the metal oxide precursor solution in step (3) is 1:(99-100); Preferably, after the mixed impregnation, a mixed impregnation liquid is first obtained, and then the mixed impregnation liquid is subjected to a second rotary evaporation and a second calcination in sequence to obtain the defective catalyst; Preferably, the temperature of the second rotary evaporation is 40 to 80°C; Preferably, the rotation speed of the second rotary evaporation is 50-80 r / min; Preferably, the heating rate of the second calcination is 8-12°C / min; Preferably, the end temperature of the second calcination is 250-350°C; Preferably, the second calcination holding time is 3 to 6 hours.
8. The preparation method according to any one of claims 4 to 7, characterized in that: The preparation method comprises the following steps: (1) mixing a titanium source and a silicon source in a molar ratio of (4.5-5.5):1 with a solvent and hydrolyzing them to obtain a titanium-silicon composite carrier suspension; then subjecting the titanium-silicon composite carrier suspension to a first rotary evaporation at 50-70°C and 50-80 r / min, and then heating the suspension to 450-650°C at a heating rate of 8-12°C / min and keeping the temperature for 3-6 hours to perform a first calcination to obtain the titanium-silicon composite carrier; The volume ratio of the sum of the titanium source and the silicon source to the solvent is 1:(2.5-3.5); (2) mixing the titanium-silicon composite support of step (1) with an alkaline solution having a concentration of 1.8 to 2.2 mol / L at a solid-liquid ratio of 1:(10 to 20) g / mL, and etching for 10 to 15 hours at 40 to 80° C. with stirring to obtain the defective titanium dioxide support; (3) impregnating the defective titanium dioxide support and the metal oxide precursor solution in step (2) at 40 to 80° C. for 1 to 3 hours to obtain a mixed impregnation solution; performing a second rotary evaporation at 40 to 80° C. and 50 to 80 r / min; then heating the temperature to 250 to 350° C. at a heating rate of 8 to 12° C. / min and maintaining the temperature for 3 to 6 hours to perform a second calcination to obtain the defective catalyst; The mass ratio of the metal oxide precursor in the metal oxide precursor solution to the defective titanium dioxide carrier is 1:(99-100).
9. A method for catalytic degradation of nitrogen-containing volatile organic matter and synergistic ammonia production, characterized in that: The method is carried out using the defective catalyst according to any one of claims 1 to 3; The method comprises the following steps: nitrogen-containing volatile organic matter is degraded through a catalytic reaction under the action of the defective catalyst to generate ammonia.
10. The method according to claim 9, characterized in that The nitrogen-containing volatile organic compound includes any one of ethanolamine, N,N-dimethylethanolamine or N,N-dimethylamide or a combination of at least two thereof; Preferably, the temperature of the catalytic reaction is 80-300°C, preferably 220-280°C.
Citation Information
Patent Citations
Low-temperature ammonia-selective oxidation catalyst and preparation method, application and use method thereof
CN109261150A
Titanium oxide@C hollow composite framework embedded with precious metal silver, and preparation method and application thereof
CN113488651A
Catalytic oxidation catalyst for waste gas containing organic amine as well as preparation method and application of catalytic oxidation catalyst
CN114682296A
Monatomic defect catalyst for CO oxidation as well as preparation method and application of monatomic defect catalyst
CN118477634A
Phosphorus-doped titanium dioxide, preparation method therefor and use thereof
WO2024198511A1
Cited By
Catalyst for ammonia production through catalytic degradation of N-VOCs in cooperation with SCR denitration and preparation method and application of catalyst
CN122098567A
A catalyst for catalytic degradation of N-VOCs to produce ammonia and SCR denitration, and a preparation method and application thereof
CN122098567B